Intra-radicular dentin treatments and retention of fiber posts with self-adhesive resin cements - André Luis Faria-; Murilo de Sousa Menezes; Fernanda Pereira Silva; Giselle Rodrigues dos Reis; Rafael Ratto de Moraes (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The aim of this study was to evaluate the effect of treating intraradicular dentin with irrigating solutions on the retention of glass-fiber posts luted with self-adhesive resin cement. Bovine incisors were endodontically treated, and 9-mm-deep postholes were prepared. Before inserting the cement, the root canals were irrigated with various solutions: 11.5% polyacrylic acid for 30 s, 17% EDTA for 60 s, or 5% NaOCl for 60 s, respectively. Irrigation with distilled water was used in the control group. After all specimens had been rinsed with distilled water, the excess moisture was removed and the posts were luted using either BisCem (Bisco) or RelyX Unicem clicker (3M ESPE). Seven days after luting, the specimens were sectioned transversally into 1-mm-thick slices, which were submitted to push-out testing on a mechanical testing machine. Bond strength data (n = 6 per group) were analyzed by two-way ANOVA and Student-Newman-Keuls' test (α = 0.05). For Unicem, EDTA showed lower bond strength than the other solutions, which had similar results. For BisCem, EDTA showed higher bond strength than the other treatments, while application of NaOCl yielded higher bond strength than polyacrylic acid whereas the control group had intermediate results. In conclusion, irrigating root canals before insertion of self-adhesive resin cements, especially EDTA, might interfere with retention of the fiber posts.